Sprint kayaking performance enhancement by isometric strength training inclusion: A randomized controlled trial - Lum, D.; Barbosa, T. M.; Balasekaran, G. (Sports, 2021)
Performing isometric strength training (IST) can enhance various sports performance. This study compared the effects of including IST on sprint kayaking performance as compared to traditional strength training. Twenty sprint kayaking athletes (age 22 ± 4 year, stature 1.71 ± 0.09 m, body mass 72.0 ± 11.4 kg) performed a 200-m kayak ergometer time trial (200mTT), isometric squat (IsoSqT), isometric bench press (IsoPress) and isometric prone bench pull (IsoPull) during the pre- and post-tests. Athletes were randomly assigned to either traditional strength training (TRAD) or IST group. Both groups performed a similar strength training program twice a week for six weeks. However, half the volume for squat, bench press and prone bench pull were replaced by IsoSqT, IsoPress and IsoPull, respectively, for the IST group. IsoSqT was performed at 90° knee angle, while IsoPress and IsoPull were performed at 90° and 120° elbow angles, respectively. Each isometric contraction was performed with maximum intensity and sustained for three seconds. A significant main time effect was observed for 200mTT (p < 0.001, Eta2p = 0.68) and all isometric strength measures (p = 0.001-0.032, Eta2p = 0.24-0.76) except rate of force development at 0-90 ms (RFD90) obtained from IsoSqT120 and IsoPress90. A group main effect was observed in RFD90 obtained from IsoSqT120 and IsoPull120 (p = 0.003-0.004, Eta2p = 0.37-0.39). Time x Group interaction was observed for 200mTT (p = 0.027, Eta2p = 0.68), peak force obtained from IsoSqT90, IsoPress90, and IsoPull120 (p = 0.004-0.006, Eta2p = 0.36-0.38) and RFD90 obtained from IsoSqT120 and IsoPull120 (p = 0.012-0.015, ?2p = 0.28-0.30). Inclusion of IST resulted in greater improvement for sprint kayaking and strength performances then TRAD alone.